PENGARUH MODEL DISCOVERY LEARNING DENGAN PENDEKATAN SAINTIFIK TERHADAP KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR - Melfi Nenchi; Eko Swistoro; Eko Risdianto (UNIB Press, 2017)
The purpose of this research is to know the effect of using discovery learning model with scientific approach to science process skill and learning outcomes. The instrument used in this research is the test. The tests in this study include pretest and posttest. The sample was taken using purposive sampling technique obtained by class XI IPA.2 as experimental class and class XI IPA.1 as control class. The result of science process skills can be seen on the difference in scores before being treated with treatment after treatment. The average pretest score for each meeting was 35.1 and the average posttest score for each meeting was 74.0 with the difference in posttest and pretest mean scores was 38.8. Based on the results of data using the t-test two independent samples indicate there is significant influence of the use of discovery learning model with scientific approach to student learning outcomes tcount 3.764 > ttable 2,004. Thus, it can be concluded that there is a significant influence of the use of discovery learning model with a scientific approach to science process skills and student learning outcomes. Keywords: discovery learning model, scientific approach, Science Process Skills and Learning Outcomes